Association between suicidal spectrum behaviors and Attention-Deficit/Hyperactivity Disorder: A systematic review and meta-analysis. (August 2019) - Septier, Mathilde; Stordeur, Coline; Zhang, Junhua; Delorme, Richard; Cortese, Samuele
Highlights: The relationship between ADHD and suicide spectrum behaviors (SSBs) is unclear. We found a significant association of ADHD to SSBs, even after controlling for possible confounders. Practitioners should systematically screen for SSBs in patients with ADHD. Abstract: The relationship between ADHD and suicidal spectrum behaviors (SSBs) remains uncertain. We conducted the first meta-analysis on the association between ADHD and SSBs taking possible confounders into account. Based on a pre-registered protocol (PROSPERO-CRD42018093003), we searched Pubmed, Ovid and Web of Knowledge databases through April 6th, 2018, with no language/publication type restrictions, and contacted study authors for unpublished data/information. From a pool of 2798 references, we retained 57 studies. Random-effects models were performed. Study quality was rated using the Newcastle-Ottawa Scale. After pooling crude ORs, we found a significant association between ADHD and suicidal attempts (2.37, 95% CI = 1.64–3.43; I 2 = 98.21), suicidal ideations (3.53, 2.94–4.25; I 2  = 73.73), suicidal plans (4.54, 2.46–8.37; I 2 = 0), and completed suicide (6.69, 3.24–17.39; I 2 = 87.53). Results did not substantially change when pooling adjusted ORs. Findings were also in general robust to sensitivity analyses to assess possible moderators. Awareness of the association between ADHD and SSBs should contribute to more effectively prevent SSBs.